Probable Maximum Sizes of Inclusions Predicted by SEV and PSD for BH Steels of Automobile Exposed Panel with Different Sulfur Contents - Xiaoqian Pan; Jian Yang (Metals, 2020)
This study attempted to estimate the maximum size of inclusions in the ultra-low carbon Bake Hardening (BH) steels of automobile exposed panel. The Probable Maximum Sizes (PMS) of inclusions at the different steelmaking stages for BH steel with different sulfur contents were predicted by two methods of Statistics of Extreme Values (SEV) and Particle Size Distribution (PSD). The S content does not show a relationship with the PMS prediction of inclusions in the molten steel in which Al2O3 is the main inclusion, while the higher content of S leads to a larger PMS value in the slab, due to more number of large-sized Al2O3-MnS inclusions formed during solidification. The PMS value in the slab is greater than that in the molten steel for BH steel. Thus, the PMS of inclusions in the slab cannot be estimated from the molten steel samples. The SEV can be used to predict well the PMS values at different steelmaking stages for BH steels. However, the PSD of exponential function cannot predict well the PMS value in the slab for BH steel when considering all kinds of inclusions due to the large influence of small-sized MnS with high number density on the PSD of exponential function. When only considering Al2O3-MnS inclusions, the PSD of exponential function can make a reasonable PMS prediction in the slab, because the size distribution of Al2O3-MnS with large size can follow the exponential function.